Pondok Pesantren Nurul Islam: Sejarah dan Perannya dalam Membina Umat Islam di Desa Pinding Kabupaten Aceh Tenggara, 1960-2000 - Patdli Irsan; Solihah Titin Sumanti; Abdi Mubarak Syam (Local History & Heritage, 2022)
This article aims to discuss the history and role of the Nurul Iman Islamic boarding school in fostering Muslims in Pinding Village, Southeast Aceh Regency in 1960-2000. The Nurul Islam Islamic Boarding School is a boarding school that was founded in 1960. Since its establishment until now, the Nurul Islam Islamic Boarding School has helped the community of Pinding village in carrying out their obligations as Muslims, including performing the 5 daily prayers. The method used in this study is a historical research method through four stages, namely the heuristic, verification, interpretation and historiography stages. Data collection techniques used in this research are observation, interviews and documentation. The results showed that the Nurul Islam Islamic boarding school is the oldest Islamic boarding school in Southeast Aceh Regency. The Nurul Islam Islamic Boarding School has developed from year to year. The Nurul Islam Islamic Boarding School has a major role in fostering Muslims in Pinding Village, Bambel District, Southeast Aceh Regency as a religious education institution, da'wah institution, and social institution.